Identification of loci associated with water use efficiency and symbiotic nitrogen fixation in soybean - Arifuzzaman, Muhammad; Mamidi, Sujan; Sanz-Saez, Alvaro; Zakeri, Hossein; Scaboo, Andrew; Fritschi, Felix B. (Frontiers in Plant Science, 2023)
Soybean (Glycine max) production is greatly affected by persistent and/or intermittent droughts in rainfed soybean-growing regions worldwide. Symbiotic N2 fixation (SNF) in soybean can also be significantly hampered even under moderate drought stress. The objective of this study was to identify genomic regions associated with shoot Carbon Isotope Ratio (δ13C) as a surrogate measure for water use efficiency (WUE), Nitrogen Isotope Ratio (δ15N) to assess relative SNF, N concentration ([N]) and carbon/nitrogen ratio (C/N). Genome-wide Association (GWA) mapping was performed with 105 genotypes and approximately four million single nucleotide polymorphism (SNP) markers derived from whole genome resequencing information. A total of 11, 21, 22, and 22 genomic loci associated with δ13C, δ15N, [N], and C/N, respectively, were identified in two environments. Nine of these 76 loci were stable across environments, as they were detected in both environments. In addition to the 62 novel loci identified, 14 loci aligned with previously reported QTL for different C and N traits related to drought, WUE, and N2 fixation in soybean. A total of 58 Glyma gene models encoding for different genes related to the four traits were identified in the vicinity of the genomic loci.